Analysis and experiment on seed-filling performance of double seed-taking precision dibbler for cotton - Zibin Mao; Luochuan Xu; Mengyu Guo; Junwei Li; Xin Luo; Bin Hu; Xiyang Li (Smart Agricultural Technology)
Aiming at the problem that cottonseeds cannot be separated and migrated from the population in time due to disordered seed-filling, short filling time, and fast seed-filling speed in the filling process of the existing mechanical precision dibbler, this paper innovated a mechanical precision dibbler for double seed-taking, in which the seed-taking disc is provided with a finite migration space that can effectively disrupt the population and assist seed-filling. It can ensure the seed-filling performance of the cotton precision dibbler at high speed (> 4 km·h-1). A numerical simulation of the seed-filling process was conducted using EDEM software, and the effects of kinetic energy and velocity of the population, moving track, and velocity of a single cottonseed on filling performance were examined. A three-factor, five-level quadratic rotational orthogonal test with rotational speed, population height, and thickness as test factors, filling index, and missing index as test indices. When the rotational speed of the seed-taking disc was 42.3 r·min-1, that is, the working speed of the planter was 4.06 km·h-1, the population height was 0.165 kg, and the thickness of the seed-taking disc was 5.5 mm, the filling index and missing index were 96.65% and 3.35%, respectively. This study not only provides a reference for the high-speed seed-filling theory of the type hole in precision dibblers but also contributes to the local seed cluster formation of ellipsoidal materials in the relative rotation space and the accelerated migration of a single target material to fill type holes.